Assessment of out-of-plane failure of non-engineered masonry walls due to Typhoon Haiyan induced storm surges - Borais, Jenes P. (Animo Repository, 2018)
Typhoon Haiyan, in 2013, caused massive destruction in eastern Luzon and central Visayan region in the Philippines. Failure (collapsed) of non-engineered masonry walls were the most common failure experienced by residential structures in the area. Local government declared No Build Zone policy along coastal barangays, however this policy was not successfully implemented due to economic and social considerations.This exposed the high vulnerability of non-engineered masonry walls, as employed in residential structures in rural areas, against extreme events. Existing building codes for large reinforced concrete (RC) frame structures had performed well during Typhoon Haiyan, however, the current construction method for masonry walls for coastal structures has high vulnerability to out-of-plane (OOP) failures due to poor construction methodology and insufficient design considerations. On-site survey along the coastal barangays of Tacloban City was conducted mainly to investigate the construction and design process for masonry walls of the low-rise residential structures. Based on this survey, a common non-engineered design was established. Adequacy of the minimum design requirement for masonry walls based on NSCP 2015/ACI 530-02 was also verified. The estimated maximum pressure capacity using yield line method for the non-engineered masonry walls and NSCP 2015/ACI 530-02 compliant design was found to be below the possible lateral pressure due to storm surges. Thus, improved construction design was proposed and assessed against similar loads with consideration about the cost and suitability for the local worker’s skills and techniques. Improvements in design includes reducing spacing and increasing the size of steel reinforcements, increasing CHB thickness, and regulating masonry wall dimensions. Comparison in lateral pressure capacity per design consideration of masonry walls were established by finite element analysis using Staad Pro V8. Based on the comparison of the analytical results, it is concluded that the maximum pressure capacity of the improved masonry design increased significantly compared to the current non-engineered masonry design.